Executive Job Demands: Suggestions from a Stress and Decision-Making Perspective - Ganster, Daniel C. (Academy of Management Review, 2005)
Hambrick, Finkelstein, and Mooney advance propositions concerning the effects of job demands on executive leadership and decision-making behaviors. I aim to encourage further thinking in this area, with comments flowing from a consideration of the stress and decision-making literature and the positive affect and problem-solving behavior literature. This perspective suggests both a finer-grained conceptualization of the executive job demands construct informed by specific characteristics of decision problems and a finer-grained conceptualization of executive decision behaviors focused on elements reflecting correspondence and coherence outcomes of decisions.